Both Maternal and Newborn IgMs Inhibit Transmissible Gastroenteritis Virus Internalization in LLC-PK1 Cells - Pogribna, A.P.; Haran, B.E.; Starosyla, D.B.; Rybalko, S.L.; Deryabin, O.M.; Syvak, V.V.; Govsieiev, D.O.; Погрібна, А.П.; Гаран, Б.Є.; Старосила, Д.Б.; Рибалко, С.Л.; Дерябін, О.М.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Immunoglobulins M (IgMs) are the evolutionally oldest class of antibodies in higher eukaryotes. This pool of antibodies is one of the first to appear in humans and begins to be-synthesized at the early stages of the neonatal period. Most of the repertoire of IgMs of the newborns consists of the so-called «natural», or «naive», antibodies synthesized by the body without external antigenic stimulation. In addition to the classical functions of human immunoglobulins M (such as antigen recognition and initiation of innate immune responses), antibodies of this class exhibit a variety of non-canonical functions. The non-canonical functions are the action of antibodies as agonists/antagonists of various receptors, cleavage of antigen due to the catalytic activity of IgM, direct inactivation of pathogens in the absence of effector cells and molecules, etc. The aim of this work was to study and compare the antiviral activity of total preparations of immunoglobulin M of newborns and adults, obtained from umbilical cord and venous blood sera, on the LLC-PK1 cell line model infected with the transmissible gastroenteritis virus (TGEV). In addition, in the course of the studies, a decision was made to investigate the effect of combined preparations of immunoglobulin M on the change in signal transduction in the epidermal growth factor receptor as one of the mechanisms of TGEV internalization during infection of target cells. Methods. Highly purified preparations of total IgM of adults or newborns were obtained using the methodologies of sequential salt fractionation and affinity chromatography. This work used the model of the interaction of the transmissible gastroenteritis virus with cells of the LLC-PK1 line and the monitoring of changes in the phosphorylation state of the epidermal growth factor receptor of these cells during virus infection to study the effect of human IgM on the internalization of the virus and its interaction with the receptor system of the host cell. The degree of cytopathogenic effect of the virus was determined visually by changes in cell morphology. The mean infectious dose for transmissible gastroenteritis virus in the cell culture of the LLC-PK1 line was determined by the Reed-Muench method. Analysis of changes in the phosphorylation of the epidermal growth factor receptor was performed using the Western-blot analysis method. Results. The addition of a total high-purified sample of human IgM reduces the degree of efficiency of TGEV infection of the LLC-PK1 cell line and modulates the phosphorylation levels of these cells. Conclusions. The total preparations of IgM obtained from human venous blood of adults and from umbilical cord blood of newborns can affect the internalization of the transmissible gastroenteritis virus in the LLC-PK1 cell line. The original model of virus (TGEV) — cell line (LLC-PK1) was applied and tested to study the effect of native total preparations of immunoglobulin M on the internalization of the virus into the cell. The obtained data can be useful in further studies for a better understanding of the process of development and functioning of the immune system of newborns.